Epidemiology of birth defects in teenage pregnancies: Based on provincial surveillance system in eastern China - Chen, Xinning; Lou, Haifeng; Chen, Lijin; Muhuza, Marie Parfaite Uwimana; Chen, Danqing; Zhang, Xiaohui (Frontiers in Public Health, 2022)
Background Healthcare for adolescents and birth defects (BD) prevention are highlighted public health issues. The epidemiology of birth defects in teenage pregnancies has not been studied extensively. Objectives To investigate the prevalence trend and spectrum of BDs among teenage mothers. Methods This observational study covered all births registered in the BD surveillance system in Zhejiang Province, China, during 2012–2018. The annual change in the prevalence of BDs among adolescent mothers was estimated. Crude relative ratios using the BD categories in teenage pregnancies were calculated and compared with those in women aged 25–29 years. Results Overall, 54,571 BD cases among 1,910,977 births were included in this study, resulting in an overall prevalence of 234.64 to 409.07 per 10,000 births from 2012 to 2018 (Ptrend < 0.001) in total population. The prevalence of birth defects in teenage pregnancies increased from 247.19 to 387.73 per 10,000 births in 2012–2018 (Ptrend = 0.024). The risks of neural tube defects (relative risk [RR] = 3.15, 95% confidence interval [CI] 2.56, 3.87), gastroschisis (RR = 7.02, 95% CI 5.09, 9.69), and multiple birth defects (RR=1.27, 95% CI 1.07, 1.52) were higher in teenage pregnancies than those in women aged 25–29 years. Conclusions We found a distinctive spectrum of BDs, with higher proportions of fatal or multiple anomalies in infants born to teenage mothers than in those born to adults aged 25–29 years. These results emphasize the importance of providing adolescents with better access to reproductive and prenatal care.